Penyuluhan Tentang Pemakaian Kontrasepsi IUD Di PMB Andina Primitasari Palembang - Dempi Triyanti; Rika Oktapianti (Jurnal Pengabdian Masyarakat Mandira Cendikia, 2024)
IUD (Intra Uterine Device) or IUD contraception is a tool or object that is inserted into the uterus that is very effective, reversible and long-term, can be used by all women of reproductive age, with the aim of contraception or pregnancy prevention efforts (Handayani, 2010). The population growth rate in Indonesia is increasing. This can be seen from the growth rate in Indonesia based on the results of the 2010 population census, the population of Indonesia is 237,556,363 people consisting of 119,107,580 men and 118,048,784 women. LPP in 2017 is expected to drop to 1.1%. (BKKBN, 2017). The low number of mothers using IUD contraception is due to the lack of information about the benefits of using IUD contraception so that the mother's attitude in choosing IUD is still very low which has an impact on actions in choosing IUD contraception. This situation greatly influences the mother's decision to use IUD contraception.IUD (Intra Uterine Device) or IUD contraception is a tool or object that is inserted into the uterus that is very effective, reversible and long-term, can be used by all women of reproductive age, with the aim of contraception or pregnancy prevention efforts (Handayani, 2010). The population growth rate in Indonesia is increasing. This can be seen from the growth rate in Indonesia based on the results of the 2010 population census, the population of Indonesia is 237,556,363 people consisting of 119,107,580 men and 118,048,784 women. LPP in 2017 is expected to drop to 1.1%. (BKKBN, 2017). The low number of mothers using IUD contraception is due to the lack of information about the benefits of using IUD contraception so that the mother's attitude in choosing IUD is still very low which has an impact on actions in choosing IUD contraception. This situation greatly influences the mother's decision to use IUD contraception.